Gender Issues in Conservation - Case of Rajaji National Park, India - Chandola, Shivani; Badola, Ruchi; Mishra, B. K. (Indian Forester, 2008)
The eco-development programme was initiated in Rajaji National Park to elicit participation of local people in conservation. An analysis of factors influencing the participation of women and men in the eco-development programme in two villages - Ganeshpur and Gangabhogpur, adjoining Rajaji National Park was carried out. On the basis of the study it is suggested that examination of all the social, cultural and economic factors that affect men's and women's ability to effectively participate in the formal forums should be done before implementing such programs thus ensuring unbiased gender representation in common forums.